1997
DOI: 10.1097/00007632-199701150-00006
|View full text |Cite
|
Sign up to set email alerts
|

A New Technique for Measuring Lumbar Segmental Motion In Vivo

Abstract: This new method offers dynamic recording capabilities and a measurement error comparable with stereo radiographic methods. Repetitive ranging experiments are highly reproducible. The range of motion for axial rotation seems overestimated in previous cadaveric studies. Coupling patterns show large variations between individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 41 publications
6
52
0
1
Order By: Relevance
“…This result confirms the findings of several studies analyzing elementary motion of the lumbar spine [3,16,18,22], although some other authors have described coupling as constant (while differing from segment to segment) and well established [15,17]. Several studies have shown that lateral bending is accompanied by rotation to the same side, but that coupling is variable during rotation [16,22]. Coupling characteristics are probably influenced by several parameters, of which lumbar lordosis and posture, muscular control and intrinsic mechanical properties are most frequently put forth [8,16,17].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result confirms the findings of several studies analyzing elementary motion of the lumbar spine [3,16,18,22], although some other authors have described coupling as constant (while differing from segment to segment) and well established [15,17]. Several studies have shown that lateral bending is accompanied by rotation to the same side, but that coupling is variable during rotation [16,22]. Coupling characteristics are probably influenced by several parameters, of which lumbar lordosis and posture, muscular control and intrinsic mechanical properties are most frequently put forth [8,16,17].…”
Section: Discussionsupporting
confidence: 91%
“…In particular, the coupling between axial rotation and lateral bending was analyzed. Although still a matter of controversy, coupling of bending and rotation during elementary trunk motion has been studied by several authors [3,8,16,17,18,22]. However, little is known about this aspect during gait, despite the fact that such information might be useful in fundamental and clinical conditions for several disorders or deformities, such as idiopathic scoliosis and chronic low back pain.…”
Section: Feipel T De Mesmaeker P Klein M Roozementioning
confidence: 99%
“…A pathologic movement of the intervertebral motion segment is considered to be the origin of symptoms [15,23,24,28]. As defined by Panjabi, lumbar instability would imply that the spine has lost the ability to maintain its pattern of displacement under physiologic loads and thus avoid neurological deficits, incapacitating deformity and intractable pain [27].…”
Section: Introductionmentioning
confidence: 99%
“…9 -11 Therefore, several invasive methods emerged with different reliability, technical difficulties, and, especially, clinical feasibility. For example, invasive methods include conventional lateral radiographs, 3-dimensional lumbar motion analyses by biplanar radiography, 12 videofluoroscopic or cineradiographic analyses, [13][14][15][16] the use of percutaneous transpedicular-external fixation pins 17,18 or Kirschner wires inserted into the spinous process, 19 and the use of open interventional magnetic resonance imaging. 20 Because the specific apparatus required and invasive nature of the aforementioned methods, to date, their use has been limited to scientific studies with small patient series investigated, except for conventional lateral radiographs.…”
mentioning
confidence: 99%
“…Because the postulated main advantage compared to fusion operation is the preservation of mobility, the quantification of movement will be of special clinical interest in future studies dealing with these techniques. Although the demonstration of coupled spinal motion is not possible and the methods are not as precise as other more invasive or technical demanding methods, 12,15,17,19 radiographs obtained in maximum flexion and extension will most likely be used more frequently to calculate the ROM of lumbar spine because of its clinical feasibility. 14,22,24 -28 Different radiologic methods have been described for the analysis of conventional flexion-extension radiographs to calculate the segmental ROM.…”
mentioning
confidence: 99%